Tissue ischemia worsens during hemodialysis in end-stage renal disease patients - Malik, Jan; Kudlicka, Jaroslav; Lachmanova, Jana; Valerianova, Anna; Rocinova, Katarina; Bartkova, Magdalena; Tesar, Vladimir (The journal of vascular access, 2017)
BACKGROUND: Cognitive deficit is a common problem in end-stage renal disease (ESRD) patients. Ultrafiltration and hemodialysis lead to profound hemodynamic changes. The aim of this pilot study was to describe brain and hand oxygenation values in ESRD patients and their changes during hemodialysis. METHODS: Twenty-seven patients treated by chronic hemodialysis and 17 controls patients of the same age were included in the study. Regional saturation of oxygen (SrO2) was measured at the brain frontal lobe and at the hand with dialysis access using the INVOS 5100C. In 17 of ESRD patients, SrO2 was also monitored throughout hemodialysis. Finger systolic blood pressure and basic hemodialysis and laboratory data were collected. RESULTS: Dialysis patients had lower brain and also hand SrO2 values at rest (51.5 ± 10.9 vs. 68 ± 7%, p<0.0001 and 55 ± 16 vs. 66 ± 8%, p = 0.03, respectively). Both values further decreased during the first 35 minutes of hemodialysis (brain SrO2 to 47 ± 8%, p<0.0001 and hand to 45 ± 14%, p<0.0001, respectively). The brain SrO2 decrease was related to the ultrafiltration rate, the hand SrO2 decrease to the finger pressure and to blood hemoglobin. CONCLUSIONS: Chronic dialysis patients suffer from tissue ischemia and that even worsens after the beginning of hemodialysis. This observation may contribute to the understanding of cognitive deficit etiology.
Keywords: Blood Flow Velocity; dospělí; čelní lalok; Frontal Lobe; senioři nad 80 let; studie případů a kontrol; Pilot Projects; ruka; Humans; lidé středního věku; mozkový krevní oběh; rychlost toku krve; Aged, 80 and over; Middle Aged; Oxygen; Regional Blood Flow; Time Factors; Cerebrovascular Circulation; Brain Ischemia; Risk Factors; mužské pohlaví; Ischemia; kognitivní poruchy; Kidney Failure, Chronic; Hand; Adult; regionální krevní průtok; výsledek terapie; rizikové faktory; časové faktory; dialýza ledvin; biologické markery; Treatment Outcome; ischemie mozku; kyslík; ženské pohlaví; Renal Dialysis; lidé; Case-Control Studies; Cognition Disorders; chronické selhání ledvin; pilotní projekty; Biomarkers; Aged; senioři; Male; ischemie; Female